Legal protection for the elderly persons: a comparative study on the existing laws and policies / Amiera Syakinah Zulkifli … [et al.] - Zulkifli, Amiera Syakinah; Nor Azwa, Nor Diana; Mohamad, Nur Suriati; Noorazmi, Mohammad Izzul Izwan (2010)
Modernization has enabled people to be able to live longer and healthier. Due to its rapid development, society has neglected the practice and custom of caring for elderly persons in their families. Nowadays, we have been moving toward the concept of individualism when more people who have elderly persons who regarded them as an additional burden to themselves or their families. Subsequently, this has led to the establishment of the National Policy for the Elderly in Malaysia. However, there has been a lack of legal enforcement of it and presently, there are no legal provisions that specifically govern the protection of elderly persons. The purpose of this study is to propose a comprehensive legislation for the legal protection of elderly persons by looking into the existing laws and policies that we have today. Apart from that, a comparison has been made between the laws of our country with laws in other countries on matters regarding the protection of the elderly persons. We will also examine the implementation of the existing laws and policies in Malaysia as a method to safeguard the protection of elderly persons. In conclusion, elderly persons must be regarded as an important entity in our society. The best care for elderly persons can only be rendered by their own family members. Caring for the elderly is our personal responsibility and not of others. Home is the best place for elderly persons to spend their golden years.